2018
DOI: 10.1111/1468-5973.12252
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between governmental communications and fellow citizens’ reactions via twitter: Experimental results of a theoretical crisis in the Netherlands

Abstract: This study aimed to gain insight into the interplay between citizens’ reactions on Twitter and governmental communications as well as their effects on self‐reliant behaviour and trust. Two experimental studies were conducted. In Study 1, participants first received other citizens’ reactions followed by the government's communications about how to act. Participants received supporting, opposing, mixed, or no reactions from other citizens. In Study 2, participants first received the government's communications w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Hong, Fu, Wu, and Frias-Martinez (2018) identified that citizens living in different areas of Maryland, USA, had different information demands during natural disasters, while the degree of matching between demand and supply determined the online communication effects between government and citizens. During crises, citizens turn to leaders and expect governments to provide prompt and accurate information (Bakker, van Bommel, Kerstholt, & Giebels, 2019). Xie, Qiao, Shao, and Chen (2017) analyzed citizens' information sharing behaviors on Sina Weibo in the context of Chinese public crises; they found that citizens were most interested in receiving information about the government's handling of the crisis and its developments.…”
Section: Media Richness and Cegsmmentioning
confidence: 99%
“…Hong, Fu, Wu, and Frias-Martinez (2018) identified that citizens living in different areas of Maryland, USA, had different information demands during natural disasters, while the degree of matching between demand and supply determined the online communication effects between government and citizens. During crises, citizens turn to leaders and expect governments to provide prompt and accurate information (Bakker, van Bommel, Kerstholt, & Giebels, 2019). Xie, Qiao, Shao, and Chen (2017) analyzed citizens' information sharing behaviors on Sina Weibo in the context of Chinese public crises; they found that citizens were most interested in receiving information about the government's handling of the crisis and its developments.…”
Section: Media Richness and Cegsmmentioning
confidence: 99%
“…During disasters, organizations can help individuals physically and psychologically cope through effective crisis communication (Coombs, ; Holladay, ; Sturges, ). Recent studies published by the Journal of Contingencies and Crisis Management also examined crisis communication during disasters (Bakker, Bommel, Kerstholt, & Giebels, ; van Dijl, Zebel, & Gutteling, ). Yet, disaster research has focused on “prevention and control through modification of the human habitat” rather than “human adaption” to risks like tornadoes (Islam, , pp.…”
Section: Introductionmentioning
confidence: 99%
“… Bakker et al. (2019) found that when government crisis communications on Twitter display certainty, they engender trust in government.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Receiving certain, rather than uncertain, information boosted recipients' certainty in their own judgment and made them more likely to use the information. In addition, an increase in certainty in one's own judgment was associated with increased self-reliance ( Bakker et al., 2019 ; Rabinovich and Morton, 2012 ). Twitter has been successfully used to provide earthquake and tsunami warnings ( Chatfield et al., 2013 ; Finch et al., 2016 ) and help first responders find areas in need quickly ( Cassa et al., 2013 ; Finch et al., 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%